What factors influence ultra-processed food purchases and consumption in households with children? A comparison between participants and non-participants in the Supplemental Nutrition Assistance Program (SNAP). (1st March 2019) - Moran, Alyssa J.; Khandpur, Neha; Polacsek, Michele; Rimm, Eric B.
Abstract: Ultra-processed foods are industrially formulated products that are convenient, highly-palatable, and contain few whole ingredients. While popular among US households regardless of SES, these foods constitute a relatively large proportion of grocery spending among low-income households participating in the Supplemental Nutrition Assistance Program (SNAP). Little is understood about the perceived factors influencing selection and consumption of these foods, particularly among households with children participating in SNAP. We conducted 5 focus groups with 45 parents of children under 18 years of age living in a low-income area of a Northeastern state. We conducted inductive-deductive thematic analysis to identify emergent themes and to identify similarities and differences by self-reported SNAP participation. Six themes related to ultra-processed food decision-making emerged, which were grouped into primarily rational or primarily intuitive processes. Rational decisions included concerns about the product's healthfulness, environmental sustainability, and desirable traits, which were each weighed against product cost when deciding between similar products. Intuitive themes included retailer marketing, household norms, and individual affective biases. The family social and emotional context and parenting practices were identified as important influences on preparation and consumption of ultra-processed foods. Differences between SNAP participants and non-participants emerged. SNAP participants selected ultra-processed foods because of their familiarity and long shelf-life – attributes that mitigated fear of wasting money on foods that may be rejected by children or spoil quickly. Some SNAP participants purchased ultra-processed foods at the beginning of the monthly benefit cycle and stored them in anticipation of food scarcity at the end of the month. These findings underscore the distinct role of ultra-processed foods in meal planning and budgeting and the importance of rational considerations that particularly affect food choices of households participating in SNAP.